The effect of G20 summits on global financial markets - Marco Lo Duca; Livio Stracca (European Central Bank (ECB), 2014)
In the wake of the global financial crisis, the G20 has become the most important forum of global governance and cooperation, largely replacing the once powerful G7. In this paper we run an event study to test whether G20 meetings at ministerial and Leaders level have had an impact on global financial markets. We focus on the period from 2007 to 2013, looking at equity returns, bond yields and measures of market risk such as implied volatility, skewness and kurtosis. Our main finding is that G20 summits have not had a strong, consistent and durable effect on any of the markets that we consider, suggesting that the information and decision content of G20 summits is of limited relevance for market participants.
Keywords: G14; G15; F53; 330; event studies; financial crisis; G20; global financial markets; global governance; volatility